Perception of time and space in life science course 2005-2018 curricula and textbooks. - ÖZÇINAR, Ayse (Turkish History Education Journal (TUHED), 2024)
This study aims to compare the Life Science curricula and textbooks of 2005 and 2018 in terms of time and space perception skills. These programs and related textbooks were analyzed and compared regarding specific objectives and content dimensions. In the study, document analysis was conducted using a case study, one of the qualitative research designs. The main data sources of the study are the 2005 and 2018 Life Science course curricula published by the Ministry of National Education TTKB and the first, second, and third-grade Life Science textbooks. According to the findings, no "specific objectives" for perceiving time and space were specified in the 2005 curriculum, but "specific objectives" focusing on these skills were identified in the 2018 curriculum. In the content dimension, it was observed that the 2005 curriculum included more achievements in perceiving time, while the 2018 curriculum emphasized the skill of perceiving space more. In the "time perception skill" category, it was stated that "conventional time" used by children in their daily lives was emphasized and chronology skill was not included in the 2018 program. "Mental transformation", which is a category of space perception skill, was found to be the least used category in both programs. These results show that the Life Science course curricula and textbooks should define this skill more clearly and make a balanced distribution in the textbooks to help students develop these skills.